2013
DOI: 10.1021/ie4012084
|View full text |Cite
|
Sign up to set email alerts
|

Gasification of Granulated Scrap Tires for the Production of Syngas and a Low-Cost Adsorbent for Cd(II) Removal from Wastewaters

Abstract: In this work, the steam gasification of scrap tires was investigated as a sustainable and cost-effective alternative to tire landfill disposal. Steam activation of the char derived from the tire residues of the gasification process was carried out at constant temperature and feeding ratio between gasifying agent and char, using different activation times (180 and 300 min). The complete characterization of all intermediate products of the processes, namely, raw material (tire), gasification products (char and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…For EOL treatments, Molino et al [23] evaluated the energetic potential of an alternative to the recycling of tires in the field of environmental protection. Such a study concluded that the steam gasification of scrap tires was found as sustainable and cost effective alternative compared to disposal in landfill.…”
Section: State Of the Artmentioning
confidence: 99%
“…For EOL treatments, Molino et al [23] evaluated the energetic potential of an alternative to the recycling of tires in the field of environmental protection. Such a study concluded that the steam gasification of scrap tires was found as sustainable and cost effective alternative compared to disposal in landfill.…”
Section: State Of the Artmentioning
confidence: 99%
“…However, they suffer from high cost, low efficiency, incomplete metal removal, high reagent and energy requirements, and the generation of secondary pollution [15]. Adsorption technology still remains attractive and represents an innovative and economical approach to arsenic removal [16][17][18].…”
mentioning
confidence: 99%
“…Many authors studied different techniques aimed to reduce toxic species in wastewater streams, which are summarized in two recent reviews (Fu and Wang 2011;Barakat 2011). Adsorption (Molino et al 2013;Di Natale et al 2015), chemical precipitation (Prisciandaro et al 2006), ion exchange, and evaporation are the most widely used techniques to remove heavy metals from aqueous effluents (Ku and Jung 2001;Alyüz and Veli 2009); however, they are not able, in some cases, to completely remove metals, they are expensive processes, and they have low selectivity (Ferella et al 2007).…”
Section: Introductionmentioning
confidence: 99%